Química forense: a utilização da química na identificação de entorpecentes - Silva, João Vitor Veloso (Universidade Federal de São Carlos, 2024)
Forensic chemistry applies scientific knowledge from the natural sciences to clarify issues of legal interest, such as theft, homicide and drug trafficking, helping to solve crimes. Drugs, which represent a major social, public health and economic problem, are the focus of public institutions which, through seizures and chemical analysis, obtain crucial information about their properties and the regions with the highest incidence of trafficking. Chemometrics, in this context, is a valuable tool, as it allows the chemical composition of narcotics to be determined, identifying impurities and adulterants that can reveal the origin of the drug and the routes used in trafficking. The aim of this paper is therefore to present the main identification methods used by criminal experts, highlighting their advantages and limitations. Among the analytical techniques used for these analyses are high performance liquid chromatography (HPLC), gas chromatography coupled with mass spectrometry (GC-MS), Fourier transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR), thin layer chromatography (TLC) and nuclear magnetic resonance (NMR). Each of these techniques offers specific advantages, such as high sensitivity, selectivity and the ability to identify unknown chemical structures in complex mixtures, but also has limitations, such as cost and the need for specialized equipment.
Forensic chemistry: the use of chemistry for the identification of narcotics
Keywords: Química Forense; Entorpecentes; Perito Criminal; CIENCIAS EXATAS E DA TERRA::QUIMICA